Vitamin D Deficiency: A Treatable but Often Forgotten Cause of Motor Delay in Infants - Kakkar, Shruti; Sahni, Suhalika Singla; Kumar, Ruchika; Goraya, Jatinder Singh (Journal of Pediatric Neurology, 2020)
Vitamin D deficiency is an under-recognized cause of motor delays in infants and young children. Retrospective chart review identified 17 infants, 11 boys and 6 girls, aged between 7 and 27 months with motor delays attributable to vitamin D deficiency. Diagnosis of vitamin D deficiency was made on the basis of clinical, radiological, and biochemical findings. Presenting symptoms were delay in motor milestones in 14 and hypocalcemic seizures in 3. On physical examination, clinical signs of rickets were present in all. Neurological examination displayed hypotonia with retained tendon reflexes. Thirteen and ten infants, respectively, underwent radiographical and biochemical investigations, and all had abnormalities consistent with rickets. All infants were treated with 6,00,000 IU of vitamin D. Four infants were lost to follow-up. Rapid recovery of motor development was observed in remaining 13 infants. Vitamin D deficiency should be considered in the differential diagnosis of motor delays in infants and young children.
Keywords: vitamin D deficiency; rickets; motor delay; infants; children